Evaluation of laboratory tests for cirrhosis and for alcohol use, in the context of alcoholic cirrhosis - Whitfield, John B.; Seitz, Helmut K. (Alcohol, 2017)
Laboratory tests can play an important role in assessment of alcoholic patients, including for evaluation of liver damage and as markers of alcohol intake. Evidence on test performance should lead to better selection of appropriate tests and improved interpretation of results. We compared laboratory test results from 1578 patients between cases (with alcoholic cirrhosis; 753 men, 243 women) and controls (with equivalent lifetime alcohol intake but no liver disease; 439 men, 143 women). Comparisons were also made between 631 cases who had reportedly been abstinent from alcohol for over 60 days and 364 who had not. ROC curve analysis was used to estimate and compare tests' ability to distinguish patients with and without cirrhosis, and abstinent and drinking cases. The best tests for presence of cirrhosis were INR and bilirubin, with areas under the ROC curve (AUCs) of 0.91 ± 0.01 and 0.88 ± 0.01, respectively. Confining analysis to patients with no current or previous ascites gave AUCs of 0.88 ± 0.01 for INR and 0.85 ± 0.01 for bilirubin. GGT and AST showed discrimination between abstinence and recent drinking in patients with cirrhosis, including those without ascites, when appropriate (and for GGT, sex-specific) limits were used. For AST, a cut-off limit of 85 units/L gave 90% specificity and 37% sensitivity. For GGT, cut-off limits of 288 units/L in men and 138 units/L in women gave 90% specificity for both and 40% sensitivity in men, 63% sensitivity in women. INR and bilirubin show the best separation between patients with alcoholic cirrhosis (with or without ascites) and control patients with similar lifetime alcohol exposure. Although AST and GGT are substantially increased by liver disease, they can give useful information on recent alcohol intake in patients with alcoholic cirrhosis when appropriate cut-off limits are used.
Gesehen am 30.10.2018